Dealing with Linguistic Problems Faced by Master’s Students in their Thesis Writing - Adnan Zaid (Ahmad Dahlan Journal of English Studies, 2016)
Upon completing all the required courses, master’s students in Indonesia are to write a thesis. Thesis writing, to some extent, haunts the students, especially when they have to conduct it in English. The problems are not only concerned with the contents of their thesis, but also with linguistic problems on how to write well with good basic command of English. The linguistic problems can cause their sentences to be not grammatically acceptable, or even sometimes not readable.This paper will explore the linguistic problems faced by master’s students in their thesis writing such as the ones related to diction, tenses, concord, articles, sentence patterns, to infinitive, gerund, and participle. It will also deal with how to solve the problems by giving the students some treatment while they are in the process of writing their thesis. The data will be taken from master’s students’ thesis drafts. The students are under the writer’s supervision.